PENGARUH DAN EFEKTIFITAS COGNITIVE BEHAVIORAL THERAPY (CBT) BERBASIS KOMPUTER TERHADAP KLIEN CEMAS DAN DEPRESI - Zakiyah, - (E-Journal Widya Kesehatan dan Lingkungan, 2014)
Abstract: Anxiety and Depression is a form of mental disorder that most commonly occurs. Care and effective treatment for anxiety disorders and depression are indispensable so that the disorder people may re-productive in meeting the needs of life, do not rely on others, and can perform daily activities. The purpose of this study was to determine the effect and the effectiveness of computer-based Cognitive Behavioral Theraphy (CBT) on anxiety and depression. The method used literature study with descriptive exploratory approach. It can be concluded that: (1) CBT is a therapy that combines of cognitive and behavioral therapy designed to change negative thought patterns into positive so that person has the ability to react adaptively in the face of problems or difficult situations in every phase of life. (2) CBT has been widely performed in patients with mental disorders quite effectively (3) CBT therapy hasn’t been applied optimally yet in patients with mental disorders, especially anxiety disorders and depression because of the limitations of cost, access, and practitioners experts in the implementation of CBT, (4) CBT is effective in reducing symptoms of depression and anxiety, and also effcient in cost.